2009
DOI: 10.1021/la9010983
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Zinc Oxide Nanorods and Nanoparticles

Abstract: A simple method for encapsulating zinc oxide nanoparticles within an organic matrix is described that consists of dispersing them in an ethanolic solution, adding an organothiol, and stirring while heating. Electron microscopy, photoemission, Raman spectroscopy, and thermal gravimetric analyses demonstrate that partial dissolution of the oxide occurs, accompanied by encapsulation within a matrix consisting of a 1:2 zinc/thiol complex. Using this methodology, it is possible to surround ZnO within diverse matric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 35 publications
5
44
0
Order By: Relevance
“…The S 2p peak located at 163.2 eV with a shoulder at 164.3 eV (Figure S2) indicates that EDT molecules were covalently bonded onto the surfaces of ZnO nanocrystals, forming zinc thiolates. [30][31][32] Figure 1c shows the O 1s core level spectra, which can be deconvoluted into two peaks. The lower-binding-energy peak is associated with the oxygen atoms in a ZnO matrix, i.e.…”
Section: Edt Treatment On Zno Nanocrystal Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S 2p peak located at 163.2 eV with a shoulder at 164.3 eV (Figure S2) indicates that EDT molecules were covalently bonded onto the surfaces of ZnO nanocrystals, forming zinc thiolates. [30][31][32] Figure 1c shows the O 1s core level spectra, which can be deconvoluted into two peaks. The lower-binding-energy peak is associated with the oxygen atoms in a ZnO matrix, i.e.…”
Section: Edt Treatment On Zno Nanocrystal Filmsmentioning
confidence: 99%
“…The more negative oxidation state of the zinc ions is consistent with the formation of Zn-S bonds, which replaces the original Zn-O bonds of the hydroxyl groups or carboxylate groups. [31] A quantitative depth-profile study on the E-ZnO films was carried out (Figure 1e). With the prolonged sputter time, the atomic ratio of sulfur to zinc is kept in the range of 0.25 to 0.29, indicating that EDT treatment effectively modified all the ZnO nanocrystals in the bulk films which are ~85 nm in thickness.…”
Section: Edt Treatment On Zno Nanocrystal Filmsmentioning
confidence: 99%
“…As shown in the S 2p spectrum of the Figure 2(a), a strong peak appeared at 163.1 eV agrees to the Zn-S covalent bond signal in literatures. [16][17][18][19] The existence of PTT on the nanorod surface was also verified with the UV-absorption spectrum (the thick solid line in Figure 2(b)). The strong absorption at 244 nm originates from PTT while the strong absorption peak at 362 nm is characteristic for ZnO nanorods.…”
Section: -15mentioning
confidence: 54%
“…We think that such a slightly roughened surface morphology originates from the dissolution of the Zn-thiol complex during the thiol grafting reaction. The mechanism of this dissolution was recently suggested by Singh et al 16 In brief, hydroxyl groups can be bonded to zinc atoms on the zinc oxide lattice (ZnO-OH) and thiol molecules (RSH) react at the hydroxylated sites, forming a zinc-thiol complex (ZnO-SR) and liberating a water molecule. This complex can readily be dissolved out into solution (Zn-SR+) and the freshly exposed ZnO surface further react with thiol molecules, which should be accelerated upon heating.…”
Section: -15mentioning
confidence: 99%
“…Various experiments, including ones in our laboratories, have demonstrated that underivatized alkanethiols chemisorb onto zinc oxide [13][14][15][16][17][18][19][20][21], and quantum mechanical modeling confirms chemisorption [22]. In contrast, however, FTIR measurements on ZnO nanotips indicate an absence of hexanethiol adsorption [23].…”
Section: Introductionmentioning
confidence: 96%